The role of governance in the evaluation of the social performance of the economic units - عبد الله حنان صحبت; عودة نجوى محمود (Journal of Economics and Administrative Sciences, 2017)
The aim of this investigation is to study and analysis the role of governance in the evaluation of the and social performance of the economic units to be addressed through the concept of corporate governance and then to the social performance and its relationship to corporate governance. The most important obtained results from this research is that the corporate governance of extreme importance, and derive their importance from being an essential tool to contribute to the transparency and fair disclosure of the financial results of economic units in the fight against financial and administrative corruption in economic units, thus providing protection and confidence of all parties, and the evaluating social performance leaves a prominent effects on the performance of employees, and levels of production, because of its large position in them, is related to the assessment of the work they perform, and the exercise of the activities. . In this lies the importance of research in the evaluation process itself, and the foundations on which it is based, and is evaluating social performance of an important means and the need for the strategy and the most appropriate in the modern framework for governance in order to lead the economic unity towards efficiency and effectiveness, and must work to link the calendar of social performance of corporate governance system.